2021
DOI: 10.1007/s10354-021-00884-0
|View full text |Cite
|
Sign up to set email alerts
|

Complications of influenza in 272 adult and pediatric patients in a German university hospital during the seasonal epidemic 2017–2018

Abstract: Summary Background The influenza season 2017–2018 of the northern hemisphere was the highest since 2001 and was caused predominantly by influenza B virus. Methods We performed a retrospective analysis of all patients in a university hospital in northern Germany with laboratory-confirmed influenza during the winter season 2017–2018 and analyzed underlying conditions, complications, and outcome. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…23 Several recently published articles have described extra-pulmonary complications in hospitalized children with influenza B prior to the COVID-19 pandemic. [24][25][26][27] Geerdes-Fenge et al treated 17 hospitalized children with influenza B in northern Germany in the winter season of 2017-2018, and revealed that 5 (29.4%) suffered extrapulmonary complications, 24 lower than 42% (37/88) found in the present study (Table 1). A few studies focusing on neurologic involvement in hospitalized children with influenza B observed that approximately 10-15% of the patients had neurologic complications.…”
contrasting
confidence: 38%
See 1 more Smart Citation
“…23 Several recently published articles have described extra-pulmonary complications in hospitalized children with influenza B prior to the COVID-19 pandemic. [24][25][26][27] Geerdes-Fenge et al treated 17 hospitalized children with influenza B in northern Germany in the winter season of 2017-2018, and revealed that 5 (29.4%) suffered extrapulmonary complications, 24 lower than 42% (37/88) found in the present study (Table 1). A few studies focusing on neurologic involvement in hospitalized children with influenza B observed that approximately 10-15% of the patients had neurologic complications.…”
contrasting
confidence: 38%
“…Influenza can cause complications outside the respiratory system in both adults and children. [21][22][23][24][25][26][27] A large series study of 2330 hospitalized pediatric patients with influenza A (H1N1 pdm09) during the 2009-2010 pandemic in the USA revealed that 709 (30.4%) children had complications affecting the digestive, neurological, musculoskeletal and cardiovascular systems. 23 Several recently published articles have described extra-pulmonary complications in hospitalized children with influenza B prior to the COVID-19 pandemic.…”
mentioning
confidence: 99%
“…The virus can directly affect the middle ear or promote fluid accumulation in the middle ear with secondary bacterial infection [8]. Ear infections, pneumonia and febrile convulsions are the most common complications of influenza in children [8,10]. The study conducted by Short KR et al have shown that normal nasopharyngeal flora, in the presence of an influenza virus infection has the ability to ascend the Eustachian tube and determine middle ear inflammation [11].…”
Section: Otitis Mediamentioning
confidence: 99%
“…Опасность развития осложнений недооценивается не только пациентами, но и врачами. Так, по данным исследователей из Северной Германии осложнения возникли у 68% взрослых пациентов с гриппом А: 40,1%пневмония, 25,3% -острое повреждение почек, 9,3%сепсис, 6,4% -инфаркт миокарда и другие осложнения, погибли 9,5% пациентов, и у 31,1% педиатрических пациентов: 16,9% -инфекции нижних дыхательных путей, 10,1% -фебрильные судороги и раздражение мозговых оболочек, отит, миозит и другие осложнения [4].…”
Section: Introductionunclassified
“…2) [8]. Интерфероновый ответ организма на введение препарата характеризуется продолжительной (до 4-5 суток) циркуляцией интерферонов в кровотоке 4 .…”
Section: Introductionunclassified